THEORETICAL ASPECTS OF WORKING WITH STUDENTS OF LOW ACADEMIC PERFORMANCE - Ravshanbek Islomov Turgunalievich (International Scientific and Current Research Conferences, 2023)
This article explores the theoretical aspects of the issue related to the work of teachers and education specialists with students with low academic performance. The article discusses various approaches to understanding and defining the concept of "low academic performance", as well as analyzes the factors influencing the formation of this problem in the modern educational environment. The author of the article examines a variety of theoretical models and techniques developed to work with students experiencing learning difficulties and discusses their effectiveness. Special attention is paid to pedagogical strategies and approaches aimed at supporting and developing students with low academic performance, as well as searching for innovative methods that can increase their motivation and interest in learning. The article also emphasizes the importance of psychological and social support for students with low academic performance, exploring the theoretical aspects of social integration and adaptation of this category of students. Finally, the authors offer recommendations for practicing teachers and education specialists based on theoretical conclusions in order to improve the learning and results of students with low academic performance.